Rethinking China Nigeria Infrastructure Financing in an Era of Economic Globalisation - Onome Odokuma; Abraham Ejogba Orhero (Pinisi Journal of Social Science, 2025)
Nigeria’s infrastructure deficit has made external financing pivotal to its development trajectory, with China emerging as a dominant partner through loans, investments, and the Belt and Road Initiative (BRI). This paper critically re-examines China-Nigeria infrastructure financing through the theoretical lenses of dependency theory and globalisation theory, exploring how structural asymmetries and global economic integration shape Nigeria’s development outcomes. Using a qualitative research design and documentary analysis, the study interrogates policy documents, institutional reports, and academic literature to evaluate the implications of Chinese-funded rail, power, and ICT projects. Findings reveal that while Chinese financing has expanded Nigeria’s infrastructural capacity and regional connectivity, it also reinforces structural vulnerabilities, including debt dependence, limited technology transfer, and weak local content participation. From a dependency perspective, these patterns reproduce unequal relations in the global capitalist system. Conversely, globalisation theory situates Nigeria’s engagement within a shifting multipolar order in which China’s growing influence redefines norms for South-South cooperation and development financing. The study concludes that Nigeria’s experience is neither purely exploitative nor wholly transformative but a negotiated outcome of global structural forces and domestic agency. It argues for a strategic rethinking of financing models centred on transparency, institutional accountability, and diversified funding sources. By recalibrating its engagement with China, Nigeria can transform infrastructure partnerships from mechanisms of dependency into instruments of industrialisation, economic sovereignty, and sustainable development in an era of global economic interdependence.